ANALISIS KELAYAKAN INVESTASI PENGEMBANGAN USAHA TWEESCAKE PALU: STUDI TRANSISI DARI GEROBAK KE TOKO FISIK - Nawas Syarif Hidayatullah; Nur Athifa; Munawarah; Muhammad Din (Publika Citra Media, 2026)
This feasibility study analyzes the expansion plan of Tweescake Palu, a micro, small, and medium enterprise (MSME) specializing in mochi sales, by establishing a physical store. The research employs a mixed-methods approach, combining quantitative and qualitative analyses. The quantitative analysis focuses on financial evaluation using five key metrics: Net Present Value (NPV), Profitability Index (PI), Internal Rate of Return (IRR), Average Rate of Return (ARR), and Payback Period (PP). The qualitative analysis is conducted through in-depth interviews with the business owner, Widya Malewa, to explore background, motivations, initial challenges, and perceptions regarding future business prospects. Based on the calculations, the investment plan is proven to be highly feasible financially. The project’s NPV is Rp37,504,178, PI is 1.38, IRR is approximately 29.82%, ARR is 27.16%, and PP is only 3.68 years, or 44.2 months, or 1,344 days. These findings confirm that the investment is financially viable to implement.